Design and In-silico Study of ¹³¹Iodium Radiolabeled of Thiourea derivatives for Breast Cancer Treatment - Miqdad Nurabdullah Al Anshari; Anindita Tri Kusuma Pratita; Ruswanto Ruswanto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Breast cancer is a serious challenge in both developed and developing countries, with current therapies still limited and potentially producing adverse side effects. To optimize breast cancer drug development, this study adopted an in-silico design approach. The aim is to develop radiopharmaceutical drugs with minimal side effects. Methods involved molecular docking analysis, molecular dynamics, drug scan, and pharmacokinetic profile prediction of the original ligan as well as the radioligand. Results showed that the radioligand had better binding energy and inhibition constant than tamoxifen as a comparator drug which is -11.31 kcal/mol and 0.00511 µM. Molecular dynamics analysis revealed that the radioligand compound exhibits comparable RMSD, RMSF, and stability metrics to the native ligand at the GRPR receptor with average RMSD and RMSF of 5.263 Å and 2.285 Å, respectively. By considering the results of these various methods, the radioligand compound shows potential as an effective radiopharmaceutical drug in breast cancer therapy.